(untitled) (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Empowering students has become one of the primary goals of education in the 21st century. The current trend of education is moving towards student-centred and independent learning. The core success of student empowerment lies in the teaching and learning approaches used to engage students. Thus, the present study aims to examine how Hikmah pedagogy, a philosophical inquiry approach, empowers students through the development of a community of inquiry and students’ inquiry skills in learning Islamic Education. Method – This study employed a case study design on a Form 4 class comprising 24 students. The method of data collection involved classroom observation and students’ reflective journaling. Analysis of classroom discourse was conducted according to Bloom’s Taxonomy to identify higher-order levels of thinking engaged by the students. Meanwhile, students’ journals were analysed thematically to examine how Hikmah pedagogy empowered their thinking. Findings – The study found that after four Hikmah pedagogy sessions, students’ thinking improved from lower-order to higher-order thinking (HOT) based on the students’ level of questions posed in the Hikmah sessions. Questions posed by the students also indicated an improvement in terms of the quantity and quality of the questions. Finally, analysis of the students’ journals showed that students found Hikmah pedagogy a provoking approach that continuously engaged them to be independent in their thinking. This is most useful when learning Islamic Education since it deals with many abstract concepts that require deep understanding. Significance – Results of the study have shown that Hikmah pedagogy can empower students by improving their HOT, developing their inquiry skills and independent thinking, which directly assist in realising the objectives of Islamic Education, which are to understand, internalise and practise Islamic principles and values.